2022
DOI: 10.1177/02611929221122780
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Different Types of Peptone as Partial Substitutes for Animal-derived Serum in Vero Cell Culture

Abstract: Vero cells are one of the most frequently used cell types in virology. They can be used not only as a vehicle for the replication of viruses, but also as a model for investigating viral infectivity, cytopathology and vaccine production. There is increasing awareness of the need to limit the use of animal-derived components in cell culture media for a number of reasons, which include reducing the risk of contamination and decreasing costs related to the downstream processing of commercial products obtained via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…For instance, several commercial peptones were utilized for optimizing the culture of CHO cells, and they resulted in encouraging effects on biomass production ( 10 ). Peptone’s ability to promote cell growth has also been reported in other studies ( 23 , 24 ). Although recombinant supplements and additives, such as growth factors, can be used in serum-free media, their utilization is not always cost-effective ( 25 ).…”
Section: Discussionsupporting
confidence: 78%
“…For instance, several commercial peptones were utilized for optimizing the culture of CHO cells, and they resulted in encouraging effects on biomass production ( 10 ). Peptone’s ability to promote cell growth has also been reported in other studies ( 23 , 24 ). Although recombinant supplements and additives, such as growth factors, can be used in serum-free media, their utilization is not always cost-effective ( 25 ).…”
Section: Discussionsupporting
confidence: 78%
“…For instance, an antibiotic may interfere with the development of cell walls, alter chromosomal topology by affecting DNA gyrase, and prevent the production of DNA, RNA, and proteins 16 . It is widely accepted that using antibiotics in cultured cells has little/no effect on gene expression 17,18 . Some research groups reported the elimination of black dots from cell culture by using Ampicillin and Gentamicin at the concentration of 50 μg/ml alone and combining these antibiotics at 100 μg/ml for five days 9, 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Transition toward animal-component free medium for Vero cell culture is also explored in this issue, by Lezin et al 3 As discussed by the authors, there are currently several serum-free formulations available for use in the proliferation and expansion of Vero cells. However, their cost can be prohibitive, and their use in culture requires careful optimisation for best cell growth.…”
Section: Editorialmentioning
confidence: 99%